Impact of popped sangyod rice on the Physicochemical and Sensory qualities of dried Krayasart bars - Langkapin, Jaturong; Parnsakhorn, Sunan; Oupathumpanont, Orawan (Asia-Pacific Journal of Science and Technology, 2025)
This study aimed to enhance the nutritional profile and sensory acceptability of dried Krayasart bars by incorporating popped Sangyod rice and stevia, and to evaluate their physicochemical and sensory characteristics. Three formulations were developed using 10.5 g, 12.5 g, and 14.5 g of popped Sangyod rice per 100 g of Krayasart mixture, with other ingredients kept constant. The optimal recipe was subsequently dried in compressed forms (2 × 2 × 2 cm and 2 × 4 × 2 cm; width × length × height) at 60, 80, and 100°C. As the amount of popped Sangyod rice increased, the L* value increased, whereas the a*, b*, and hardness values tended to decrease. Final moisture content decreased as the amount of popped rice increased. The formulation containing 10.5 g of popped Sangyod rice per 100 g of Krayasart received the highest customer satisfaction score. Consequently, formulation 1 (with 10.5 g of popped Sangyod rice per 100 g) was selected for testing in the drying process at 60°C, 80°C, and 100°C. The results indicated that the initial moisture content was 11.51% wb; after drying, it decreased to 7.36-9.34% wb for the 2 x 2 x 2 cm and 8.02-9.52% wb for the 2 x 4 x 2 cm samples. The water activity values in each sample were less than 0.65. Higher drying temperatures increased the a*, b*, and hardness values but decreased the L* value. The highest sensory test scores for both sizes of Krayasart were achieved at a drying temperature of 80°C.